Up & down : the adventures of John Jeffries, first American to fly - Brown, Don, 1949- (Charlesbridge, 2018)
"Swept up by the European ballooning craze of the 1780s, Dr. John Jeffries longed to become the first person to fly across the English Channel. But first he had to outwit a rascally copilot, keep the balloon from bursting, and avoid crashing into the sea. The good doctor's quick-thinking solutions will surprise young readers--and keep them giggling."--Amazon.com.